Plan de negocio para la creación de una empresa de desarrollo y comercialización de software de monitoreo y control de proyectos de construcción para pequeñas y medianas empresas en el Ecuador - Muñoz Navas, César Andrés (2019)
Level Up is a business that arises from the need to achieve an effective monitoring and control in the construction projects of the country. Through the development and commercialization of a computer software solution that automates the registration, processing and analysis activities of field information, it is possible to simplify and optimize the monitoring and control processes in order to introduce them in organizations in a systematic and smoothly way. In Ecuador there are 28,678 companies engaged in construction activities, 6,929 of them are in Pichincha, 1,310 of these are small and medium construction companies. In this segment in particular the business aims to reach companies that have a low performance in their construction projects, whether there are public or private projects; whose managers belong to the first "Y" generations or the last "X" generations; and that do not have a clear knowledge about the monitoring and control processes or that know about monitoring and control processes, but have not been able to effectively put them into practice. According to the above, it is expected to start with a 1.3 porcent market share, continuing with a 5 porcent monthly growth until the third year and a 5.5 porcent from the fourth year onwards. Therefore, it is estimated for the business to start generating profits from the third year, as the investment in marketing as well as sales increases. Thus, it is planned to capture at least 269 customers from the target market by the end of the fifth year with an average of three annual software subscriptions per customer. In order to accomplish this, the business foresees the need to finance $100,000 dollars, half of these to be invested in the development of the software and the other half to be used as working capital for the first two years, managing a capital structure of 50 porcent debt and 50 porcent capital. Based on the 5-year financial evaluation the project has a positive NPV equal to $ 27,096 dollars and an IRR equal to 22 porcent which is higher than the minimum expected value of 15 porcent.